Significance of plasma fibrinogen level and antithrombin activity in sepsis: A multicenter cohort study using a cubic spline model. Issue 181 (September 2019) - Matsubara, Tsunehiro; Yamakawa, Kazuma; Umemura, Yutaka; Gando, Satoshi; Ogura, Hiroshi; Shiraishi, Atsushi; Kushimoto, Shigeki; Abe, Toshikazu; Tarui, Takehiko; Hagiwara, Akiyoshi; Otomo, Yasuhiro; Fujimi, Satoshi; et al.
Abstract: Introduction: Sepsis leads to coagulopathy by the activation of inflammatory mediators and vascular endothelial cell injury. A number of biomarkers are used to evaluate coagulopathy on sepsis. Fibrinogen and antithrombin activity have been reported as biomarkers of coagulopathy; however, the utility of these two markers has not been well established. This study aimed to evaluate the detailed association between these two markers and clinical outcomes in sepsis patients. Materials and methods: This was a post hoc analysis of a multicenter, prospective cohort study conducted in 59 intensive care units throughout Japan from January 2016 to March 2017. We included 1103 adult patients with severe sepsis based on the Sepsis-2 criteria. The associations between the coagulation markers and in-hospital mortality were examined using linear and non-linear logistic regression analyses. We also evaluated the associations between the coagulation markers and disseminated intravascular coagulation (DIC) scores. The International Society on Thrombosis and Haemostasis overt DIC score was calculated after subtracting the fibrinogen component. Results: The decreased levels of the fibrinogen and antithrombin activity were significantly associated with an increase in mortality ( P  = 0.011 and 0.002, respectively). In addition, cubic spline regression demonstrated that mortality sharply increased at a fibrinogen level of approximately <200 mg/dL and at an antithrombin activity of approximately <50%. Similarly, the decreased levels of the two markers non-linearly correlated with the elevation of DIC score. Conclusions: The fibrinogen level and antithrombin activity should be reconsidered as unique biomarkers for sepsis and sepsis-induced DIC. Highlights: A cubic spline model assessed nonlinear associations between markers and outcomes. Fibrinogen levels of <200 mg/dL sharply increased the risk of mortality. Antithrombin activity of <50% sharply increased the risk of mortality. Fibrinogen and antithrombin were also non-linearly associated with DIC severity.